Implementasi Pertanian Ramah Lingkungan Berbasis Leisa (Low External Input Sustainable Agriculture) Pada Usaha Tani Padi Sawah Di Desa Setiris Kecamatan Maro Sebo Kabupaten Muaro Jambi - Ulma, Riri Oktari; Elwamendri, Elwamendri; Damayanti, Yusma; Fitri, Yanuar; Fathoni, Zakky (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2023)
The use of inorganic fertilizers and synthetic pesticides is increasingly varied in type and dosage, but increasing the dosage of fertilizer and pesticides used is not able to stimulate rice growth, in fact increasing the dosage of inorganic fertilizer further reduces rice production yields. To reduce the use of chemicals in plant cultivation, it can even be done using a low external input sustainable agriculture (LEISA) agricultural system. The LEISA concept prioritizes the use of local resources as raw materials for the development of agricultural inputs. This service program aims to assist the community in implementing LEISA-based environmentally friendly agriculture in lowland rice farming in Setiris Village, Maro Sebo District. The approach method used is counseling and training, as well as mentoring and community empowerment (farmer groups). The results of this service activity show that the people involved can adopt and implement it on their farming land and increase productivity significantly.